Conjugated Molecular Nanotubes. Issue 34 (7th May 2021) - Mirzaei, Saber; Castro, Edison; Hernández Sánchez, Raúl
Abstract: Molecular compounds with permanent tubular architectures displaying radial π‐conjugation are exceedingly rare. Their radial and axial delocalization presents them with unique optical and electronic properties, such as remarkable tuning of their Stokes shifts, and redox switching between global and local aromaticity. Although these tubular compounds display large internal void spaces, these attributes have not been extensively explored, thus presenting future opportunities in the development of materials. By using cutting‐edge synthetic methodologies to bend aromatic surfaces, large opportunities in synthesis, property discovery, and applications are expected in new members of this family of conjugated molecular nanotubes. Abstract : Synthetic efforts to bend aromatic surfaces have had a remarkable evolution during the last dozen years. Conjugated nanorings and nanobelts are among the most well‐known examples. However, this progress has also led to the synthesis of molecular compounds with permanent tubular shapes with radial and axial π surfaces, which are the highlight of this Minireview.